PENGARUH KEMAMPUAN PEMBELAJARAN ORGANISASI TERHADAP KINERJA KEUANGAN MELALUI INOVASI PRODUK SEBAGAI VARIABEL MEDIASI - Ivana Chrestella; Devie Devie Devie (Business Accounting Review, 2018)
This study aimed to know the impact of organizational learning capability on financial performance through product innovation. This research used 33 manufacturing companies (PT) in Surabaya and its surrounding areas as samples. The data then processed by using SmartPLS software version 3.0. Organizational learning capability measured by using five key dimensions: experimentation, risk-taking, interaction with the external environment, dialogue, and participative decision-making. The company's financial performance measured by using six indicators: ROA, ROE, sales growth, profitability, profit growth, and market share. Product innovation measured by using two main dimensions: effectiveness and efficiency of innovation. The result of this research implied that organizational learning capability had positive and significant affect to financial performance and product innovation, product innovation also had positive and significant affect to financial performance, and product innovation could be an intervening variable between organizational learning capability and financial performance.